Altered co-stimulatory and inhibitory receptors on monocyte subsets in patients with visceral leishmaniasis. - Emebet Adem; Endalew Yizengaw; Tadele Mulaw; Endalkachew Nibret; Ingrid Müller; Yegnasew Takele; Pascale Kropf (Public Library of Science (PLoS), 2024)
Visceral leishmaniasis (VL) is a neglected tropical disease caused by parasites from the Leishmania (L.) donovani complex. VL is characterised by uncontrolled parasite replication in spleen, liver and bone marrow, and by an impaired immune response and high systemic levels of inflammation. Monocytes have been poorly characterised in VL patients. The aim of this study was to evaluate the expression levels of markers involved in the regulation of T cell responses on different subsets of monocytes from the blood of VL patients and healthy non-endemic controls (HNEC). Monocytes can broadly be divided into three subsets: classical, intermediate and non-classical monocytes. Our results show that the percentages of all three subsets stayed similar at the time of VL diagnosis (ToD) and at the end of anti-leishmanial treatment (EoT). We first looked at co-stimulatory receptors: the expression levels of CD40 were significantly increased on classical and intermediate, but not non-classical monocytes, at ToD as compared to EoT and HNEC. CD80 expression levels were also increased on intermediate monocytes at ToD as compared to EoT and HNEC, and on classical monocytes only as compared to HNEC. The levels of CD86 were similar at EoT and ToD and in HNEC on classical and intermediate monocytes, but significantly higher at EoT on non-classical monocytes. We also looked at an inhibitory molecule, PD-L1. Our results show that the expression levels of PD-L1 were significantly higher on all three monocyte subsets at ToD as compared to HNEC, and to EoT on classical and intermediate monocytes. These results show that monocytes from the blood of VL patients upregulate both co-stimulatory and inhibitory receptors and that their expression levels are restored at EoT.